Analysis On Optimization Operation Of Cold End Of 600MW Wet Cooling Sub-critical Air Cooling Unit. (October 2020) - Shengxiang, Jin; Liuhu, Wang; Jinsong, Zhang; Qi, Zhang; Qianyu, li; Wei, Bai; Chuan, He; Yong, Zhou; Daming, li; Yu, Xiao
Abstract: Due to its remarkable water-saving characteristics, direct air cooling device has been widely used in carbon rich and water deficient areas in China. However, in the high temperature period in summer, the exhaust pressure of air cooling unit will rise greatly, the exhaust steam temperature will be high and the condensate temperature will be high. In this paper, Daihai Power Plant Phase I unit transformation as the research object, the cold end optimization of air cooling unit is analyzed, in order to improve the unit operation economy.